Spatial gene expression maps of the intestinal lymphoid follicle and associated epithelium identify zonated expression programs. - Noam Cohen (Public Library of Science (PLoS), 2021)
The intestine is lined with isolated lymphoid follicles (ILFs) that facilitate sampling of luminal antigens to elicit immune responses. Technical challenges related to the scarcity and small sizes of ILFs and their follicle-associated epithelium (FAE) impeded the characterization of their spatial gene expression programs. Here, we combined RNA sequencing of laser capture microdissected tissues with single-molecule transcript imaging to obtain a spatial gene expression map of the ILF and its associated FAE in the mouse small intestine. We identified zonated expression programs in both follicles and FAEs, with a decrease in enterocyte antimicrobial and absorption programs and a partial induction of expression programs normally observed at the villus tip. We further identified Lepr+ subepithelial telocytes at the FAE top, which are distinct from villus tip Lgr5+ telocytes. Our analysis exposes the epithelial and mesenchymal cell states associated with ILFs.